Clinicopathological Findings and Prognosis in Canine Cases Diagnosed As Primary Hypoplasia of the Portal Vein - Akiyoshi, Makoto; Hisasue, Masaharu; Akiyoshi, Masami (Frontiers in Veterinary Science, 2017)
Canine primary hypoplasia of the portal vein (PHPV) is a microscopic malformation of the hepatic vasculature. The prevalence, clinical signs, and clinicopathological findings of PHPV in dogs are unclear, because there are few reports concerning PHPV in the veterinary literature. This retrospective study reviewed clinical records and liver biopsy data from 48 dogs with hepatic disease that were examined at a private veterinary hospital in Japan between April 2011 and March 2014 to determine the prevalence of PHPV among dogs that underwent liver biopsy and to determine the clinical and clinicopathological findings of PHPV in dogs. Records for all 48 dogs that underwent liver biopsy were investigated. Collected data included signalment, clinical signs, physical examination findings, complete blood cell count, chemistry results, pre-and postprandial serum total bile acid concentrations, coagulation profiles (prothrombin time, activated partial thromboplastin time, fibrinogen, and antithrombin), and abdominal ultrasonography findings at the first medical examination. The diagnosis of PHPV was made on the basis of histological examination of hepatic biopsy specimens and portography or CT angiography. Among the 48 canine cases, 28 dogs (58.3%) were diagnosed with PHPV, which was the most common diagnosis. The most frequent clinical sign in dogs with PHPV was asymptomatic persistently increased liver enzymes (57.1%). Toy poodles were at a significantly higher risk of PHPV than other breeds among dogs that underwent liver biopsy (P<0.001). The median survival time of dogs with PHPV was more than 5 years. Plasma fibrinogen concentration below the reference range was an indicator of PHPV in this study. Dogs with PHPV frequently had mild clinical signs and a favorable prognosis.